The role of miRNAs in the development of cholangiopathies. Part 2 - A.E. Abaturov; V.L. Babуch (Zaslavsky O.Yu., 2023)
The role of miRNA in the development of cholangiopathies is considered in the scientific review. This article discusses the role of miRNA in biliary atresia, polycystic liver disease, and cholangiocarcinoma. To write the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library databases. The results of experimental studies indicate that the influence of miRNA causes the development of biliary atresia. It is found that, according to the results of miRNA expression profiling of extrahepatic bile ducts and gallbladder, miR-133a/b, miR-30b/c, miR-200a, miR-195, miR-365 and miR-320 are involved in the pathogenesis of biliary atresia. The article states that the scientists demonstrated a high level of ADD3 mRNA expression in the liver tissue of patients with biliary atresia. ADD3 overexpression promotes the adhesion and accumulation of epithelial cells in the bile ducts, which can lead to obstruction of the bile ducts and cholestasis. In turn, an excess of bile acids stimulates the proliferation of cholangiocytes and causes the development of liver fibrosis. Given that hyperproliferation of epithelial cells of the bile ducts due to an impaired cell cycle is a key feature of cystogenesis in polycystic liver disease, researchers hypothesized that miRNAs, changing the cell cycle, may contribute to hepatic cystogenesis. The authors showed that polycystic liver disease is accompanied by a decrease in the expression of miR-15a, whose target is the mRNA of the cell division cycle 25A regulator. Numerous miRNAs are involved in the development of cholangiocarcinoma, changes in the expression and content of which in blood serum were noted in patients with this form of neoplasms. Thus, after a comprehensive review using the latest information search databases, it was found that in the modern scientific literature, the authors determine the association of micro-RNA generation activity and the development of cholangiopathies, namely: biliary atresia, polycystic liver disease, cholangiocarcinoma.